2002
DOI: 10.1016/s0895-7061(01)02286-5
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of endocardial endothelial dysfunction by folic acid in homocysteinemic hypertensive rats

Abstract: The role of L- and D-isomers of homocysteine (Hcy) in vascular versus endocardial endothelial (EE) remodeling and function is not well understood. The hypothesis is that Hcy decreases EE cell density by activating matrix metalloproteinase (MMP) and by inducing left ventricular hypertrophy (LVH) in homocysteinemic hypertensive rats (HHR). And L- and D-isomers of Hcy have differential effects in vessel and myocardium. We used: 1) spontaneously hypertensive rats (SHR) in which endogenous total homocyst(e)ine (tHc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 20 publications
4
80
1
2
Order By: Relevance
“…29) Finally, the development of myocardial fibrosis and matrix metalloproteinase activity was increased in rats with high levels of homocysteine. [26][27] In this study, however, no differences in the peak creatine kinase or troponin T levels, which indicate infarct size, were observed between the two groups. Therefore, heart failure was caused not only by direct myocardial damage resulting from AMI, but also occurred after AMI associated with potential cardiac dysfunction, including left ventricular remodeling, induced by elevated plasma homocysteine levels.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…29) Finally, the development of myocardial fibrosis and matrix metalloproteinase activity was increased in rats with high levels of homocysteine. [26][27] In this study, however, no differences in the peak creatine kinase or troponin T levels, which indicate infarct size, were observed between the two groups. Therefore, heart failure was caused not only by direct myocardial damage resulting from AMI, but also occurred after AMI associated with potential cardiac dysfunction, including left ventricular remodeling, induced by elevated plasma homocysteine levels.…”
Section: Discussioncontrasting
confidence: 59%
“…However, possible causes include vascular endothelial dysfunction, [17][18][19][20][21][22] smooth muscle cell growth, [23][24][25] and an increase in blood clotting activity in vascular walls. 26,27) Elevated homocysteine levels may promote heart failure through 4 potential mechanisms. First, as described above, an elevated homocysteine level is widely considered a risk factor for coronary arteriosclerosis and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…31 Miller et al showed that folic acid treatment reduced, in part, the MMP activity at 66 and 72 kD (MMP-2). 32 Narin et al concluded that even folic acid treatment alone may be sufficient for decreasing the negative effects of homocysteine. 33 Hagar suggested that hyperhomocysteinemia aggravates myocardial infarction via oxidative stress mechanisms and that lowering the homocysteine level with folic acid and vitamin B12 can ameliorate the detrimental effects of hyperhomocysteinemia and may reduce the risk of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the cardiac ring preparation separated the effect of LV from RV. To determine the specific regional differences in contractile function, the rings can be prepared to include or to exclude the homogenous or inhomogeneous regions of the transmural myocardial wall [31,32,33,34]. The "deli" shaped LV rings were mounted in a tissue myobath.…”
Section: Urinary Proteinmentioning
confidence: 99%